Effects of moisture and pH on supercritical fluid extraction of cocoa butter - Jinap, Selamat; Kusnadi, Asep Edi; Akanda, Md. Jahurul Haque; Abdul Rahman, Russly; Ferdosh, Sahena; Sarker, Md. Zaidul Islam (Springer, 2013)
The effects of moisture content and alkali treatment on cocoa butter extraction using supercritical fluid were studied. Ground cocoa nibs were examined at moisture contents of 1.95 %, 3.91 %, 5.87 %, 9.79 % and 17.64 % and the pH ofthe cocoa liquor was maintained at 5.0–5.9, 6.8–7.2 and 7.5–7.9. Cocoa butter was successfully extracted, using supercritical carbon dioxide (SC-CO2) for the moisture content study and SC-CO2 with 25 % ethanol as a cosolvent for the pH-level alkali treatment study, at 35 MPa, 60 °C and 2 ml/min. The results showed that increases in moisture content and pH level significantly (p<0.05) increase the yield efficiency. A moisture content of 9.79 % and pH-alkali treatment at 7.5–7.9 produced the highest yield (60.36 % and 73.70 % at 20 and 18 h extraction time, respectively). Triglycerides (TG) and fatty acids (FAs)were similar to those found in cocoa butter obtained using the Soxhlet method. Saturated and short-chain TG and FA constituents were more soluble than unsaturated and long-chain constituents.